Mandal commission report : a critical appraisal - Das Veena (New Delhi, 1990)
In the wake of the announcement by the National Front Government in early August that it would implement the recommendations of the Mandal Commission regarding reservations of jobs to the extent of 27% for Other Backward Classes, there has been a great deal of anger and protest articulated by the student community. Public debate has focused on the merits and demerits of reservations and views have been rather too easily divided between two camps of 'pro-reservationists' and 'anti-reservationists'. We believe that the issues are complex: they raise some major questions regarding the role and responsibility of the state in formulating and communicating questions of policy. In order for a rational discussion to take place on these issues, it is important that objective information on the Mandal Commission Report becomes available. We believe that informed discussions are at the heart of democratic decision making. This document has been prepared to facilitate this kind of discussion. As teachers of the University of Delhi, we feel that is our duty to place before the Indian people an informed view of the Mandal Commission report so that the processes of democratic dialogue can be sustained and it is reasoned discussion that becomes the basis for reviewing major policy decisions.
Keywords: Backward classes India